Deformability of ascending thoracic aorta aneurysms assessed using ultrafast ultrasound and a principal strain estimator: In vitro evaluation and in vivo feasibility. Issue 3 (28th January 2022) - Wang, Diya; Chayer, Boris; Destrempes, François; Gesnik, Marc; Tournoux, François; Cloutier, Guy
Abstract: Background: Noninvasive vascular strain imaging under conventional line‐by‐line scanning has a low frame rate and lateral resolution and depends on the coordinate system. It is thus affected by high deformations due to image decorrelation between frames. Purpose: To develop an ultrafast time‐ensemble regularized tissue‐Doppler optical‐flow principal strain estimator for aorta deformability assessment in a long‐axis view. Methods: This approach alleviated the impact of lateral resolution using image compounding and that of the coordinate system dependency using principal strain. Accuracy and feasibility were evaluated in two aorta‐mimicking phantoms first, and then in four age‐matched individuals with either a normal aorta or a pathological ascending thoracic aorta aneurysm (TAA). Results: Instantaneous aortic maximum and minimum principal strain maps and regional accumulated strains during each cardiac cycle were estimated at systolic and diastolic phases to characterize the normal aorta and TAA. In vitro, principal strain results matched sonomicrometry measurements. In vivo, a significant decrease in maximum and minimum principal strains was observed in TAA cases, whose range was respectively 7.9 ± 6.4% and 8.2 ± 2.6% smaller than in normal aortas. Conclusions: The proposed principal strain estimator showed an ability to potentially assess TAA deformability, which may provide an individualized and reliable evaluation method for TAA rupture risk assessment.